Liberation theology : a critical analysis - Vegel, Zoltan (Array, 2018)
In this paper, we will explore liberation theology as defined by Gustavo Gutierrez, who is considered to be its founder. We will use it as an example to show how secular philosophy, and Marxism in particular, can influence Christianity and create new theological directions and movements. Also, we will see if there are some of its principles which we can freely accept as Christians, and which of them do we need to take with a grain of salt.